β‐RA reduces DMQ/CoQ ratio and rescues the encephalopathic phenotype in Coq9R239X mice - Agustín Hidalgo‐Gutiérrez; Eliana Barriocanal‐Casado; Mohammed Bakkali; M Elena Díaz‐Casado; Laura Sánchez‐Maldonado; Miguel Romero; Ramy K Sayed; Cornelia Prehn; Germaine Escames; Juan Duarte; Darío Acuña‐Castroviejo; Luis C López (EMBO Molecular Medicine)
Abstract Coenzyme Q (CoQ) deficiency has been associated with primary defects in the CoQ biosynthetic pathway or to secondary events. In some cases, the exogenous CoQ supplementation has limited efficacy. In the Coq9R239X mouse model with fatal mitochondrial encephalopathy due to CoQ deficiency, we have tested the therapeutic potential of β‐resorcylic acid (β‐RA), a structural analog of the CoQ precursor 4‐hydroxybenzoic acid and the anti‐inflammatory salicylic acid. β‐RA noticeably rescued the phenotypic, morphological, and histopathological signs of the encephalopathy, leading to a significant increase in the survival. Those effects were due to the decrease of the levels of demethoxyubiquinone‐9 (DMQ9) and the increase of mitochondrial bioenergetics in peripheral tissues. However, neither CoQ biosynthesis nor mitochondrial function changed in the brain after the therapy, suggesting that some endocrine interactions may induce the reduction of the astrogliosis, spongiosis, and the secondary down‐regulation of astrocytes‐related neuroinflammatory genes. Because the therapeutic outcomes of β‐RA administration were superior to those after CoQ10 supplementation, its use in the clinic should be considered in CoQ deficiencies.